Reflections on microbial genetic resources in agricultural systems - Iván Pável Moreno-Espíndola; Alonso Gutiérrez-Navarro; Diana Carolina Franco-Vásquez; Daniel Vega-Martínez (Current Research in Microbial Sciences)
This paper reflects on the use of microbial genetic resources in the context of agricultural systems. The benefits of harnessing the diversity of these resources in any agricultural system are highlighted, as well as the importance of knowing and preserving native agrobiodiversity, which is deemed an essential resource for Latin America. In this region, harmful effects of irrational use of agrochemicals and monocultures on the environment, economy, and health have been brought to light. In view of the growing awareness and global interest in the development of bioinputs, rational biodiversity use, environmental crisis, cost of conventional synthetic inputs, and the right to safe and quality food, agriculture requires new tools and effective strategies in its practice. Microbial genetic resources are a potential source of relevant and suitable inputs for this purpose. Using the bibliometric technique of co-occurrence of terms with the VOSviewer tool, an analysis of 60 articles published between 2020 and 2024, collected from databases such as Scopus and Web of Science, was performed. An interest in microbial resources and their potential application in plant nutrition, production of growth regulators, defenses against pests and diseases, and tolerance to limiting environmental conditions can be appreciated. However, elucidating their complex ecological dynamics is necessary to understand them in real production contexts, thus allowing the allocation of relevant technological packages and the fair management of their use and potential benefits.